(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Preparation of pregnant women in the third trimester for childbirth is an important aspect to support safe childbirth and reduce anxiety due to limited knowledge about relaxation techniques, including oxytocin massage. This study aims to analyze the relationship between the application of video digital educational media about oxytocin massage with the readiness of pregnant women in the third trimester in delivering childbirth at the Juniarsih Midwife Independent Practice, Patumbak District, Deli Serdang Regency, in 2026. This study used a correlational analytical design with a cross-sectional approach. The study population was all pregnant women in the third trimester, totaling 30 respondents selected using a total sampling technique. Data were collected using a delivery readiness questionnaire covering physical, psychological, knowledge, and logistical aspects, then analyzed using the Fisher’s Exact Test with α = 0.05. The results showed that 16 of 18 respondents (88.9%) who received the educational video had good delivery readiness, while in the group without education only 6 of 12 respondents (50.0%) had good readiness. Statistical tests showed p = 0.034 (p < 0.05), so there is a significant relationship between the application of digital educational media in the form of oxytocin massage videos and the readiness of pregnant women in the third trimester to handle childbirth.